Asking Consent for a Procedure - Win May; Beverly Wood (Association of American Medical Colleges, 2008)
Abstract This resource is a standardized patient case used to assess the interpersonal and communication skills of a resident who is asking a patient to consent to a procedure. It has been used with radiology residents but is applicable to any residency program where residents need to consent a patient. This case has been used in two residency programs and has received positive comments from the residents. The standardized patient should be concerned about the procedure and what would be happening to him/her as well as whether it could be cancer.